Improvement of soil quality through biochar in rice under wastewater irrigated soil: Effects on heavy metals reduction - Sayon Mukherjee; Satish Kumar Singh; Raimundo Jiménez Ballesta; Abhik Patra; Surendra Singh Jatav (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Rice, a global staple, can accumulate high levels of heavy metals especially Chromium (Cr) when grown in a soil irrigated with tannery effluent over time, potentially reaching toxic levels for human consumption. Biochar offers a cost-effective solution by binding these heavy metals in soil, reducing their bioavailability and mitigating health risks. The present study offers a two-way solution of reducing weed load of agricultural fields through parthenium biochar preparation and its application in Cr contaminated soil with aim of its lower accumulation in the edible part of the crop.